Debates on Religious Studies In the Phenomenology Perspective and Its Contribution to Interfaith Tolerance - Akhiyat Akhiyat (Ulumuna, 2019)
The phenomenological approach in religious studies has played an essential role in uncovering the mysteries of religious experience. With the epoché concept, which refers to the meaning of "delaying all judgments", or it can be said as meaning with the intention of suspending an understanding, that is interpreted as "confinement" (bracketing), the researcher must temporarily let go of all his judgments or understanding of the phenomenon under study to obtain universal knowledge that is transcendental to the phenomenon of religion and experience the essence that they obtain. However, critics from experts for this phenomenological approach to religion still exist, in this case, summarized in three points: first, about the continuity of the phenomenology of religion as a philosophical tradition. Second, hidden theological assumptions or motives behind the phenomenological approach of religion. Third, what is the involvement of religious scientists in the public role as social scientists face current social and political realities or the challenges of religious scientists whether they accept the public role or do not face the reality of various problems faced by society.